Pelayanan Makanan dan Minuman Pada Pesta Pernikahan Masyarakat Adat Sebagai Daya Tarik Pariwisata Berbasis Masyarakat - Ramdah Radjab; Dewa Made Dirga; I Nyoman Arcana; Mandra .; Herlina .; Rizda Endean N. Batubara (JURNAL GASTRONOMI INDONESIA, 2020)
The diversity of ethnic groups in Indonesia creates a diversity of cultural expressions. Among them are the Baduy Luar Tribe in Kanekes Village, Banten Province, Toba Batak Tribe which occupying Samosir Island, North Sumatra, and Sasak Tribe on Lombok Island. This study aims to examine the tradition of food and beverage service at traditional weddings of indigenous peoples as a community-based tourism attraction, which includes the procession of food and beverage service preparation This study resulted in the following findings, namely: 1. The philosophy implied in the stages of the third wedding party shows that the culture of the Toba Batak people is influenced by Dutch (European) culture, while the culture of the Baduy Luar community is influenced by the natural environment where they live from generation to generation., and the culture of the Sasak people combines well with the relationship between customs and Islamic culture, and; 2.Indicators of food and beverage service at the wedding of the Toba Batak, Baduy Luar, and Sasak people that have the potential to become community-based tourism. This study recommends that the preparation of wedding party food and beverage services in traditional communities apply the CHSE standard for the health of the guests and families of the bride and groom, as well as to fulfill the requirements to become a community-based tourism attraction.